Australian health system restructuring – what problem is being solved? - Dwyer, Judith M (BioMed Central, 2004)
BACKGROUND: In recent years, Australian state and territory governments have reviewed and restructured the health systems they lead and regulate. This paper examines the outcomes of the most recent official published reviews of systems and structures; identifies the common themes; and addresses two questions: what problems are being addressed? And how would we know if the changes were successful? RESULTS: In all the broad, systemic reviews, the main health system problems identified were money, hospital utilisation and a weak primary health care system. The solutions are various, but there is a common trend towards centralisation of governance, often at state health authority level, and stronger accountability measures. Other common themes are hospital substitution (services to avoid the need for admission); calls for cooperation across the Commonwealth:state divide, or for its abolition; and the expected range of current efficiency and effectiveness measures (eg amalgamate pathology and support services) and ideas in good currency (eg call centres). The top-down nature of the public review process is noted, along with the political nature of the immediate catalysts for calling on a review. CONCLUSION: The long-standing tension between the pull to centralisation of authority and the need for innovation in care models is heightened by recent changes, which may be counterproductive in an era dominated by the burden of chronic disease. I argue that the current reforms will not succeed in achieving the stated goals unless they make a difference for people with chronic illness. And if this is correct, the most useful focus for evaluation of the success of the reforms may be their impact on the system's ability to develop and deliver better models of care for this growing group of patients.